Motivating personnel creative potential - Zakharchyn, H. M.; Lyubomudrova, N. P. (Publishing House of Lviv Polytechnic National University, 2015)
This article discusses the motivational aspects of personnel creative potential in today's conditions, which is a driving force for innovation. Also the objective reasons that forced staff to develop creative potential of each company, in particular, the basic principles of formation of motivational policy for the development of creativity of staff are highlighted. The presented research shows the relationship between typology of staff work and the character of motivation, as well as determines the effectiveness of the enterprise staff creative potential motivation on the basis of various motivational tools. The efficient processes of transformation will be successful only in case of the availability of creative potential of personnel able to produce innovative ideas, to support presence of the enterprise on the innovation market and to ensure its competitiveness through unconventional management solutions. Creativity is a natural human characteristic, however, subject to certain circumstances; it is not always possible to utilize it as a driving power in innovative development of an enterprise. Because of the lack of proper motivational policy, creativity often remains just a personal condition, and there is only nominal development and use of its potential. Thus, a contradiction emerges between the objective need to implement the personal creative impulse and subjective obstacles to human development.
Keywords: motivation; motivation policy; creative potential; creativity; innovativeness; stimulating